2015
DOI: 10.1589/jpts.27.581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise therapy on muscular strength in firefighters with back pain

Abstract: [Purpose] The purpose of this study was to determine how an exercise program focusing on muscular strength could aid firefighters with chronic lower back pain. [Subjects] The research subjects were randomly assigned to two groups, the experimental group (n=8) and the control (n=8). [Methods] The experimental group performed two types of exercise programs four times per week for 8 weeks under supervision. Tests were performed before and after the 8 weeks of exercise in accordance with the Korea Occupational Saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…The present study showed that back extension strength improved sharply after 8 weeks of training, but no further gain was observed from mid-to post-intervention tests. These results are in line with the literature that 6-8 weeks of exercise training can induce substantial improvement in strength (Moon et al, 2015;Schoenfeld et al, 2015;Steele et al, 2015;Haun et al, 2019;Tay et al, 2019). Given the relatively short duration of 8 weeks, it is believed that most of the initial strength improvement are of a neurological nature rather than muscle hypertrophy (Balshaw et al, 2017).…”
Section: Improvement In Strength and Fatigabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…The present study showed that back extension strength improved sharply after 8 weeks of training, but no further gain was observed from mid-to post-intervention tests. These results are in line with the literature that 6-8 weeks of exercise training can induce substantial improvement in strength (Moon et al, 2015;Schoenfeld et al, 2015;Steele et al, 2015;Haun et al, 2019;Tay et al, 2019). Given the relatively short duration of 8 weeks, it is believed that most of the initial strength improvement are of a neurological nature rather than muscle hypertrophy (Balshaw et al, 2017).…”
Section: Improvement In Strength and Fatigabilitysupporting
confidence: 90%
“…Traditionally, conventional resistance training emphasizes symmetrical exercises whereby the left and right limbs are loaded together and perform the same range of motion simultaneously (bench press, back squat, deadlift, strict press) (Beach et al, 2014;Moon et al, 2015). These conventional exercises, when performed at appropriate intensity and volume, may provide sufficient back and core strength to protect the emergency responders from back injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness training is expected to maintain job performance. Moon et al (2015) investigated physical fitness and back pain between experimental and control groups of firefighters for 8 weeks and found that pain could be reduced in participants with chronic lower back pain after they participated in the intervention. The possible explanation for differences in findings on this variable could be that physical fitness in Moon et al’s study measured fitness and strength using stronger measures (i.e., sit-ups holding and sit-arch back holding compared with this study, which used running or walking, bench press, sit-up, and sit and reach) as measures of physical fitness.…”
Section: Discussionmentioning
confidence: 99%
“…These results have been reported among other occupational groups (e.g., nurses and construction workers) as well; however, additional research is needed on firefighters (White et al, 2016). Moon et al (2015) found that the role of physical fitness is critical to improving muscle strength and minimizing lower back pain in firefighters. Because work-related back pain is the leading cause of early retirement among firefighters, research on physical fitness and back pain in firefighters is needed (Lusa et al, 2015).…”
mentioning
confidence: 99%
“…Structured exercise interventions are beneficial for firefighter health and fitness 7,[12][13][14][15][16][17][18][19][20] ; however, only 27% of fire departments provide such programs. 2 On-site (within the station) firefighter exercise facilities and programs are often sparse, leaving individual firefighters responsible for their own physical fitness and occupational readiness.…”
mentioning
confidence: 99%